2012
DOI: 10.1177/1010539512466425
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Brain-Based Learning and Animated Cartoons for Enhancing Healthy Habits Among School Children in Khon Kaen, Thailand

Abstract: The objective of this study was to investigate the effectiveness of brain-based learning (BBL) and animated cartoons on video compact discs (VCDs) in enhancing the healthy habits of school children. A representative sample of 1085 school children in the first through the third grades at 16 schools was selected by multistage random sampling. Knowledge of healthy habits and self-reported adoption of practices were assessed by a questionnaire. BBL and VCD, either combined or as single-intervention techniques, led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…The findings of this study are consistent with the results of previous studies which revealed that the Brain-Based Teaching Approa-ch could lead to a remarkable improvement in student academic achievement (Bawaneh et al, 2012;Banchonhattakit et al, 2012;Fazil & Saleh, 2016;binti Mazlan, 2017;Saleh & Subramaniam, 2018). The findings are also consistent with the results of previous studies (Coletta et al, 2012;Kost et al, 2009), which show that male students outperform female students in Physics conceptual understanding, particularly in Force and Motion related topics.…”
Section: Methodssupporting
confidence: 92%
“…The findings of this study are consistent with the results of previous studies which revealed that the Brain-Based Teaching Approa-ch could lead to a remarkable improvement in student academic achievement (Bawaneh et al, 2012;Banchonhattakit et al, 2012;Fazil & Saleh, 2016;binti Mazlan, 2017;Saleh & Subramaniam, 2018). The findings are also consistent with the results of previous studies (Coletta et al, 2012;Kost et al, 2009), which show that male students outperform female students in Physics conceptual understanding, particularly in Force and Motion related topics.…”
Section: Methodssupporting
confidence: 92%
“…A previous study among young children on how they spend their time was revealed that as the age advances television viewing time decreases. 12 In the present study, 35% of children were interested in playing outside of The same study revealed that children less than two years of age spend more than 1.5 hours per day for television viewing. Another study in US had revealed that children below six years spend an average of about two hours a day with screen media, which is about the same amount of time they spend for playing outside.…”
Section: Discussionsupporting
confidence: 57%
“…The teachers waited for the classes and collaborated, reporting the anxiety and expectancy of the children, who actively participated in the activities. This receptiveness demonstrates that the Cartoon Program was very attractive and caught the attention of the students, as it is a playful and easy-to-use tool 43 .…”
Section: Discussionmentioning
confidence: 93%